Utilization of personal protective equipment and the hygiene sanitation practices of farmers in the application of pesticides - G. Fizulmi; H. Agustina (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Pesticides are toxic and dangerous materials requiring good handling. Pesticide exposure highly affects farmers'' health, especially spray pesticides, which arise from pesticide residues in food, air, and the environment. This research aims to determine the relationship between behavioral factors in using Personal Protective Equipment and individual hygiene and sanitation of farmers who experience health problems. This study also looks at the predictive value of farmers'' behavioral factors regarding health problems.METHODS: The design of this study is cross-sectional with quantitative research type. This study gathered 91 respondents in Jonggol Village, which has the largest agricultural land in Bogor Regency and with farmers who actively use pesticides. Accordingly, this location has a population at risk of pesticide exposure. This study used questionnaires to obtain information about farmer behavior and health problems. It also used the statistical package for the social sciences application to analyze data based on the chi-square test and multiple logistic regression.FINDINGS: The bivariate analysis results show a significant relationship between the habit of using personal protective equipment (masks) and farmers'' health problems, with a test value of 0.019 and an odds ratio of 4.24. The habit of not using hand protection (gloves) is also significantly related to not showering after farming, with a test value of 0.045 and an odds ratio of 3.61. Meanwhile, the variable habit of using hand protection (gloves) has the highest influence, with a test value of 0.008. Farmers who do not use hand protection are 17.5 times more likely to experience health problems than farmers who use hand protection. Meanwhile, the Logistic Model shows that all variables lack a significant relationship.CONCLUSION: Based on the overall analysis of the behavior of using personal protective equipment and personal hygiene of farmers, this study suggests increasing synergy between agricultural and health instructors in building awareness of using protective equipment and the correct and appropriate use of pesticides among farmers. In a cross-program and cross-sector manner, agricultural extension workers can explain how to wear protective equipment and use pesticides correctly, while health educators can promote pesticide exposure pathways and preventive measures for pesticide-related diseases. Exploring other factors influencing farmers'' willingness to use protective equipment and maintain personal hygiene is also essential, including barriers preventing farmers from behaving well. Good pesticide use behavior will maintain the health of farmers and build the health of farmer families and the surrounding community.